Pola Konsentrasi Spasial Industri Jawa Tengah Menuju Konvergensi Pembangunan - Luthfi Rezang Roy Vansyah; Prayudi Setiawan Prabowo (Jurnal Ekonomika : INDEPENDEN, 2022)
This study aims to determine the pattern and level of industrial spatial concentration in Central Java, the condition of the lowest economic growth among the six provinces in Java Island in 2021, accompanied by development inequality such as infrastructure and income per capita, for this reason an economic development strategy is needed to reduce inequality. and optimizing economic growth by looking at the pattern and potential of industrial spatial concentration or industrial agglomeration that occurs in Central Java Province, where industrial agglomeration is calculated based on the Balassa index. The results of this study indicate that there are 16 urban districts that have a spatial industrial concentration level of more than equal to 1 percent or have the potential to be developed and 1 district with a moderate level of agglomeration or i.e. more than equal to 2 percent and 18 other urban districts classified as not having agglomeration, shown below. Central Java where the pattern of industrial agglomeration shows what is called the Williamson hypothesis and negative cumulative causation, where there is a decreasing trend in cities and an increasing trend in regencies.